POWER QUALITY IMPROVEMENT IN SOLAR FED CASCADED MULTILEVEL INVERTER USING ANFIS CONTROLLER - Dr.V.Sekar, Ms.V.R.Shanmugapriya, Mr.M.Praveen (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The presence of harmonics in solar Photo Voltaic (PV) energy conversion system results in deterioration of power quality. To address such issue, our paper aims to investigate the elimination of harmonics in a solar fed cascaded fifteen level inverter with aid of Proportional Integral (PI), Artificial Neural Network (ANN) and Fuzzy Logic (FL) based controllers. Unlike other techniques, the proposed ANFIS based approach helps in obtaining reduced harmonic distortions that intend to an enhancement in power quality. This paper also proposed to provide output voltage regulation in terms of maintaining voltage and frequency at the inverter output end in compatible with the grid connection requirements. The simulations are performed in the MATLAB Simulink environment for solar fed cascaded 15 level inverter incorporating ANFIS based controllers. To exhibit the proposed technique, a photovoltaic plant coupled to multilevel inverter is designed and hardware is demonstrated. All the three techniques are experimentally investigated with the measurement of power quality metrics along with establishing output voltage regulation.